An Early mediaeval coin-hoard from Kartuzy in Pomerania - Chabrzyk, Piotr (Acta Archaeologica Lodziensia, 2018)
Coin circulation within the territory of the present-day Polish state was characterized in the early middle ages by its transboundary nature. During the reign of the first rulers of the Piast dynasty the indigenous coin production only served as a supplement to the great amount of monetary silver that was reaching our lands from the north and west. German coins flowed in from both of these directions. In 1951 the numismatic collection of the Museum of Archaeology and Ethnography in Lodz received a hoard from Kartuzy or nearby, which possibly formed part of a larger find. All of the surviving coins from this hoard are of type V according to the classification of M. Gumowski. Their obverse bears a cross surrounded by pearls, and, in the rim, various letters. Archival research shows that these coins are probably a part of a hoard that did not survive intact down to our times. One cannot be absolutely certain, however, that the deposit came from the vicinity of Kartuzy.